Pengembangan Aplikasi Mobile Health Berbasis Android untuk Monitoring dan Evaluasi Stunting - Atika Hendryani; Ernia Susana (Poltekkes Kemenkes Padang, 2020)
In 2018 Indonesia still ranked fifth as the country with the highest number of stunting in the world. A better level of a mother’s knowledge can decrease about 4% to 5% in the possibility of stunting in children. Efforts to increase maternal knowledge about the importance of preventing stunting in the first thousand days of life are not only the responsibility of the government, especially the Ministry of Health. The mass media are also responsible for providing knowledge to mothers. One of the most widely used media in accessing news and information is through mobile devices such as mobile phones. From this background the problem of this research can be formulated is how to build an Android-based mobile health application for monitoring and preventing stunting. The purpose of this research is to build an Android-based mobile health for stunting monitoring and prevention. The research method is Research and Development consists of two stages, the Research Phase using qualitative methods and the Development Phase using FAST system development methods. The research was conducted at the Poltekkes of the Ministry of Health Jakarta II, Department of Electromedical Engineering from January to December 2019. The results of the study are android mobile health applications for monitoring and evaluating stunting. From the result of system testing, the mobile health application for monitoring and evaluating stunting could work well.